2014
DOI: 10.1590/s1516-14392014005000033
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of stimuli-sensitive copolymers by RAFT polymerization: potential candidates as drug delivery systems

Abstract: Poly(2-(dimethylamino)ethylmethacrylate-b-methymethacrylate) (PDMAEMA-b-PMMA) poly(2-block copolymers were obtained by reversible addition-fragmentation chain transfer (RAFT) polymerization, and the effect of the solution pH on the particle size was investigated. In the case of PDMAEMA-b-PMMA, PDMAEMA was first synthesized using 2-cyanoprop-2-yl dithiobenzoate (CPDB) as a chain transfer agent (CTA), which was subsequently used for the RAFT polymerization of MMA. The triblock copolymers were obtained using PDMA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 19 publications
0
4
0
2
Order By: Relevance
“…Only a few CRP techniques can properly mediate the radical polymerization of NVCL, including reversible additionfragmentation chain transfer (RAFT) [16][17][18][19][88][89][90][91][92][93][94][95], a combination of ring-opening polymerization (ROP) and RAFT [96,97], atom transfer radical polymerization (ATRP) [98], and Cobalt mediated radical polymerization (CMRP) [20,29,66]. Devasia et al [88] reported the first sequential RAFT polymerization to prepare block copolymers of A c c e p t e d M a n u s c r i p t 25 polymerization.…”
Section: Block Copolymersmentioning
confidence: 99%
See 1 more Smart Citation
“…Only a few CRP techniques can properly mediate the radical polymerization of NVCL, including reversible additionfragmentation chain transfer (RAFT) [16][17][18][19][88][89][90][91][92][93][94][95], a combination of ring-opening polymerization (ROP) and RAFT [96,97], atom transfer radical polymerization (ATRP) [98], and Cobalt mediated radical polymerization (CMRP) [20,29,66]. Devasia et al [88] reported the first sequential RAFT polymerization to prepare block copolymers of A c c e p t e d M a n u s c r i p t 25 polymerization.…”
Section: Block Copolymersmentioning
confidence: 99%
“…Nevertheless, when PNVCL is used as MCTA (first step) the results suggested that polymerization in the second step did not proceed in a living manner (e.g., PNVCL-b-PtBA-b-PNVCL, M n =18 900 g/mol, Đ = 1.9). The same research group demonstrated the synthesis of ABA triblock copolymers containing PNVCL and the pH sensitive base PDMAEMA[94]. PDMAEMA and PNVCL MCTA´s were prepared using a DBTTC bifunctional RAFT agent, and were used to obtain triblock copolymers with PNVCL in the center or at both ends of the triblocks.…”
mentioning
confidence: 99%
“…Dispersities were still quite high for a controlled process (trueM¯n of 36 200–59 600 g mol −1 , trueM¯w/trueM¯n of 1.38–1.44). Recently, the same group also reported the copolymerization of NVCL with another 2‐(dimethylamino)ethylmethacrylate (DMAEMA) monomer via RAFT with the same CTA (CTA‐4), and triblock copolymers of PDMAEMA‐ b ‐PNVCL‐ b ‐PDMAEMA and PNVCL‐ b ‐PDMAEMA‐ b ‐PNVCL (trueM¯n of 11 200–19 600 g mol −1 , trueM¯w/trueM¯n of 1.58–1.90) were also described . Moderate control over the RAFT polymerization of NVCL was later reported using other CTAs, such as CTA‐5 and CTA‐6,[76b] CTA‐7 and CTA‐8 .…”
Section: Synthesis Of Well‐defined Pnvcl‐based (Co)polymers By Contromentioning
confidence: 99%
“…While the size of A 45 B 101 C 27 nanoparticles did not change for pH values 6.0–7.4, A 45 B 110 C 37 nanoparticles increased their size in this pH range. The increase of the hydrodynamic radius upon increase of the pH is associated with the decrease of the electrostatic repulsions, which induces a starting of an aggregation process of the small nanoparticles. , The aggregation process can lead to a probable sedimentation of big aggregates as indicated by the SLS experiments (Figure S4). The equilibrium between the two fractions of nanoparticles is shifted toward the smaller nanoparticles (Figure S2B).…”
Section: Resultsmentioning
confidence: 96%